Construcciones Subjetivas Alrededor del Desplazamiento Forzado en Cuatro Integrantes de la Comunidad Indígena Yanacona (2021)
The present research, whose main objective was to understand the way in which the subjective representations of four adults of the Yanacona community have been characterized in the face of forced displacement, was constituted from the theories of the Galtung conflict, History of Forced Displacement and Armed Displacement. Colombian conflict according to the Center for Historical Memory, the theory of cultural ethnicity according to Hall, Social Constructionism according to Gergen and Bruner, the postulates of the Social Representations of Ibáñez, and Subjectivity according to Galtung and González.